2016
DOI: 10.15420/cfr.2016:3:3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrates as a Treatment of Acute Heart Failure

Abstract: Acute heart failure (AHF) presents symptoms primarily the result of pulmonary congestion due to elevated left ventricular (LV) filling pressures with or without reduced ejection fraction (EF). Common precipitating pathology includes coronary artery disease (CAD), hypertension and valvular heart diseases, in addition to other noncardiac conditions, such as diabetes, anaemia and kidney dysfunction. 1,2Additionally, AHF poses major medical and socioeconomic burdens.It represents the most common discharge diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…Our subgroups analyses extensively failed in detecting any clinical setting with a more favourable setting for IV-NTG use in patients with AHF. Despite many authors have suggested that prompt initiation of IV-NTG in patients with severe pulmonary congestion (presenting in the form of acute pulmonary oedema) could be beneficial especially if it is quickly provided in the prehospital arena [8,[23][24][25], our subgroup analysis considering signs/symptoms of congestion separately according to whether they correspond to pulmonary or systemic congestion did not support this hypothesis, at least with respect to an improvement in patient survival. Similarly, age, sex, CAD as comorbidity and SBP did not have a different impact on the effects of NTG on patient survival.…”
Section: Discussioncontrasting
confidence: 74%
“…Our subgroups analyses extensively failed in detecting any clinical setting with a more favourable setting for IV-NTG use in patients with AHF. Despite many authors have suggested that prompt initiation of IV-NTG in patients with severe pulmonary congestion (presenting in the form of acute pulmonary oedema) could be beneficial especially if it is quickly provided in the prehospital arena [8,[23][24][25], our subgroup analysis considering signs/symptoms of congestion separately according to whether they correspond to pulmonary or systemic congestion did not support this hypothesis, at least with respect to an improvement in patient survival. Similarly, age, sex, CAD as comorbidity and SBP did not have a different impact on the effects of NTG on patient survival.…”
Section: Discussioncontrasting
confidence: 74%
“…However, the improper use of diuretics causes renal dysfunction and electrolyte abnormalities during clinical acute heart failure . In recent years, the contribution of congestion due to a redistribution of circulating blood has been shown to contribute to clinical pulmonary edema, and initial treatment using a vasodilator is recommended for cases of adaptation . In clinical heart failure, vascular endothelial dysfunction is often seen, and the bioavailability of NO is decreased .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In recent years, the contribution of congestion due to a redistribution of circulating blood has been shown to contribute to clinical pulmonary edema, and initial treatment using a vasodilator is recommended for cases of adaptation. 37,38 In clinical heart failure, vascular endothelial dysfunction is often seen, and the bioavailability of NO is decreased. 39,40 Use of a sGC activator, which is an endothelial-functionimproving agent that is independent of NO, is considered reasonable in treating ADHF, if hypotension can be avoided by appropriate use.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous nitroglycerin is also commonly used in acute heart failure to provide rapid dyspnea relief. Relevant mechanisms of nitroglycerin in acute heart failure include reducing myocardial strain, and hemodynamic benefits resulting in decreased right ventricular and left ventricular filling pressures (Alzahri et al, 2016). By enhancing effects of NOmediated signaling, an sGC stimulator might also be expected to favorably affect the heart.…”
Section: Cardioprotective Effects Of Olinciguatmentioning
confidence: 99%